Increasing base-station anonymity through illusive void formation. (8th May 2020) - Boulaiche, Mehdi; Younis, Mohamed
A wireless sensor network consists of a set of nodes connected by wireless links. These nodes probe their surroundings and send their data over multi-hop routes to a base-station (BS) for processing. The BS further interfaces the network to remote command centres. Given the critical role that the BS plays, it becomes a natural target for adversary attacks. Although cryptographic primitives and anonymous routing protocols can hide the identity of the BS, the traffic pattern in the network degrades the BS location anonymity and makes it vulnerable. In this paper, we propose an approach for formation of illusive void for increased BS anonymity (FIVA). FIVA exploits the features of geographic routing to confuse the adversary about the routing topology. Specifically, FIVA opts to construct a fake void around the BS and gets nodes to forward packets to encounter such a void. The goal is to exclude the BS from all traceable data paths in order to avert the adversary attention away from the BS vicinity. FIVA is validated through simulation and is shown to outperform prominent competing anti-traffic analysis techniques.